Input and output inventories - Brad R. Humphreys; Louis J. Maccini; Scott Schuh (The Johns Hopkins University, Department of Economics, 2000)
This paper presents a new stage-of-fabrication inventory model with ordering usage and stocking of input materials that distinguishes between gross production and value added It extends the traditional linear-quadratic model of output (finished goods) inventories by adding joint determination of input inventories which largely have been ignored Empirically input inventories are more important than output inventories especially in business cycle fluctuations Maximum likelihood estimation of the decision rules yields relatively strong support for the model using data for nondurable and durable good industries The value added specification outperforms gross production because adjustment costs on the change in materials usage are critical to fitting the data.
Keywords: E22; E23; 330; Inventories; raw materials; work-in-process; nished goods; stage-of-fabrication; gross production; value added; linear-quadratic; Lagerhaltungsmodell; Betriebswirtschaftliche Produktionstheorie; Theorie